Model problem based learning untuk meningkatkan kemampuan pemecahan masalah matematis siswa SMP kelas VIII - Rezqy, Muhammad; Rohaeti, Euis Eti; Sariningsih, Ratna (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research aims to see the results of increasing mathematical problem solving abilities using the problem based learning model. The method used in this research is a quantitative method with a quasi-experimental type of research and uses a Nonequivalent Control Group design. The sample in this study was 20 students from each class. Class VIII B is the experimental class and class VIII D is the control class. The data collection technique in this research uses written test instruments, namely pretest and posttest. Data management in this research began with a test of students' mathematical problem solving abilities, namely using a pretest and posttest. After that, the data from the pretest and posttest results were processed by carrying out the t-test and Ngain test. The results of this research show that the problem based learning model can improve students' mathematical problem solving abilities. The conclusion of the research shows that the problem based learning model is better than ordinary learning for improving students' mathematical problem solving abilities.